An Increased Ratio of Glycated Albumin to HbA1c Is Associated with the Degree of Liver Fibrosis in Hepatitis B Virus-Positive Patients. (17th February 2014) - Enomoto, Hirayuki; Aizawa, Nobuhiro; Nakamura, Hideji; Sakai, Yoshiyuki; Iwata, Yoshinori; Tanaka, Hironori; Ikeda, Naoto; Aoki, Tomoko; Yuri, Yukihisa; Yoh, Kazunori; Hashimoto, Kenji; Ishii, Akio; et al.
Abstract : Background . In hepatitis B virus- (HBV-) positive patients, the relationship between the metabolic variables and histological degree of liver fibrosis has been poorly investigated. Methods . A total of 176 HBV-positive patients were assessed in whom the ratios of glycated albumin-to-glycated hemoglobin (GA/HbA1c) were calculated in order to investigate the relationship with the degree of liver fibrosis. Results . The GA/HbA1c ratio increased in association with the severity of fibrosis (METAVIR scores: F0-1: 2.61 ± 0.24, F2: 2.65 ± 0.24, F3: 2.74 ± 0.38, and F4: 2.91 ± 0.63). The GA/HbA1c ratios were inversely correlated with four variables of liver function: the prothrombin time (PT) percentage (P < 0.0001 ), platelet count (P < 0.0001 ), albumin value (P < 0.0001 ), and cholinesterase value (P < 0.0001 ). The GA/HbA1c ratio was positively correlated with two well-known markers of liver fibrosis, FIB-4 (P < 0.0001 ) and the AST-to-platelet ratio index (APRI) (P < 0.0001 ). Furthermore, the GA/HbA1c showed better correlations with two variables of liver function (PT percentage and cholinesterase value) than did FIB-4 and with all four variables than did the APRI. Conclusion . The GA/HbA1c ratio is associated with the degree of liver fibrosis in HBV-positive patients.